Rock magnetic study on the Yetti-Eglab intrusions, Sahara: Contribution to the West African Craton geology. - (:unkn) unknown (My University, 2021)
New palaeopoles have been calculated for the West African Craton (WAC) using palaeomagneticdata obtained on 178 cores of the Yetti–Eglab intrusions and stromatolite-bearing formation. One, two orthree components of magnetization on 172 (14 sites) and 37 (6 sites) oriented specimens or cores were isolatedmainly on doleritic dykes. High and low unblocking temperature components were evidenced in the dykes butalso at four sites of the well-dated Hank stromatolite-bearing formation (875–890 Ma). Rock magnetic analysesshow stable remanent magnetizations mainly carried by magnetite (or titanomagnetite) but may also reveal thepresence of hematite, pyrrhotite and goethite. Regarding the recently constructed apparent polar wander path ofthe WAC until 500 Ma, these newly computed remanent components seem to be mainly older, some of whichcould be remagnetizations at different periods. However, according to geological dating and literature, the Yettiand Eglab terranes belonging to theWACwere amalgamated around 1.9 Ga and involved in the formation of theColumbia Supercontinent. The palaeopole computed for the stromatolite-bearing formation corresponds with thelocation of Rodinia Supercontinent at its early stages of amalgamation. The geodynamic evolution of the WACwith respect to both supercontinents suggests that the Eglab and Yetti could be separated by oceanic crust before1.9 Ga. A volcanic arc developed during the subduction of this ocean followed by crustal thickening that generatedan intrusive suite (Aftout granites) when it was at low northern latitudes. Baltica and Rio de la Plata cratonswere close to the WAC after 1.7 Ga, following a nearly similar path between 1.7 and 0.9 Ga. In Africa, the collapseof the Birimian orogen was probably contemporaneous with the fragmentation of Columbia. At 0.9 Ga,Baltica was probably not attached to the WAC since the latter was not affected by the later Grenvillian orogen.
Keywords: African Research